Falsified medicines in Africa: all talk, no action - Newton, Paul N. (2014)
Poor-quality medicines and medical products, both substandard and falsified, cause avoidable morbidity, mortality, drug resistance, and loss of faith in health systems, especially in low-income and middle-income countries.1–3 We report the analysis of two falsifi ed medicines from Angola and discuss what lessons such a discovery could hold.